A biologically-assisted curved muscle model of the lumbar spine: Model validation. (August 2016) - Hwang, Jaejin; Knapik, Gregory G.; Dufour, Jonathan S.; Best, Thomas M.; Khan, Safdar N.; Mendel, Ehud; Marras, William S.
Abstract: Background: Biomechanical models have been developed to predict spinal loads in vivo to assess potential risk of injury in workplaces. Most models represent trunk muscles with straight-lines. Even though straight-line muscles behave reasonably well in simple exertions, they could be less reliable during complex dynamic exertions. A curved muscle representation was developed to overcome this issue. However, most curved muscle models have not been validated during dynamic exertions. Thus, the objective of this study was to investigate the fidelity of a curved muscle model during complex dynamic lifting tasks, and to investigate the changes in spine tissue loads. Methods: Twelve subjects (7 males and 5 females) participated in this study. Subjects performed lifting tasks as a function of load weight, load origin, and load height to simulate complex exertions. Moment matching measures were recorded to evaluate how well the model predicted spinal moments compared to measured spinal moments from T12/L1 to L5/S1 levels. Findings: The biologically-assisted curved muscle model demonstrated better model performance than the straight-line muscle model between various experimental conditions. In general, the curved muscle model predicted at least 80% of the variability in spinal moments, and less than 15% of average absolute error across levels. The model predicted that the compression and anterior–posterior shear load significantly increased as trunk flexion increased, whereas the lateral shear load significantly increased as trunk twisted more asymmetric during lifting tasks. Interpretation: A curved muscle representation in a biologically-assisted model is an empirically reasonable approach to accurately predict spinal moments and spinal tissue loads of the lumbar spine. Highlights: The model fidelity of a curved muscle model was evaluated in complex lifting tasks. The curved muscle model showed good model fidelity between experimental conditions. Spinal loads were sensitive to the various physical lifting conditions examined. A curved muscle model will be useful to accurately predict complex spinal loads.